Programming industrial control systems using IEC 1131-3 - Lewis, R. W. (Robert W.) (Institution of Engineering and Technology, 1998)
This revised edition includes all IEC proposed amendments and corrections for the planned 1999 revision of IEC 1131-3, as agreed by the IEC working group. It accurately describes the languages and concepts, and interprets the standard for practical implementation and applications.